2019
DOI: 10.20524/aog.2019.0413
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full-thickness resection of gastric gastrointestinal stromal tumor: a Japanese case series

Abstract: Background:Gastrointestinal stromal tumors (GISTs) are potentially malignant and are indicated for resection. The standard treatment for resectable GISTs is surgery, although endoscopic resection has been reported outside Japan. This study retrospectively analyzed the results of endoscopic resection of GISTs in Japan.Method:We identified patients with GISTs treated only by endoscopic resection in our institute between January 2016 and December 2018, and analyzed their clinical and pathological characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…GISTs do not have a well-defined capsule; therefore, in cases of R1 resection, it is necessary to perform scar tissue removal, for example, by using (EFTR) with a dedicated Ovesco ® set (Tübingen, Germany). By comparison, Shichijo et al [ 15 ] presented the results of an alternative hybrid variant of the EFTR technique using elements of ESD, clipping, and ligating with endoloop. In 62% of the tumours, the resection margins were indeterminate, even in cases of deep resections followed by perforation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GISTs do not have a well-defined capsule; therefore, in cases of R1 resection, it is necessary to perform scar tissue removal, for example, by using (EFTR) with a dedicated Ovesco ® set (Tübingen, Germany). By comparison, Shichijo et al [ 15 ] presented the results of an alternative hybrid variant of the EFTR technique using elements of ESD, clipping, and ligating with endoloop. In 62% of the tumours, the resection margins were indeterminate, even in cases of deep resections followed by perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the long-term efficacy of GIST removal by ESD is controversial, especially in cases of gastric wall defects and tumour ruptures [ 19 ]. The most common complications include perforations, which occur in 1.2–9.7% of cases, and bleeding (up to 15% cases) [ 12 , 14 , 15 , 17 , 18 , 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 11 retrospective cohort studies reporting short and mid-term outcomes of exposed EFTR of gastric SMTs, as summarized in Table 3. [47][48][49][50][51][52][53][54][55][56][57] Majority of the resected SMTs were confirmed to be GIST histologically. While the sample size of each series is still small, the published data demonstrated high complete resection rate (90.3%-100%).…”
Section: Endoscopic Full-thickness Resectionmentioning
confidence: 97%
“…Despite the rapid development of endoscopic treatment in Japan, few authors have reported on the use of endoscopic treatments for gastrointestinal mesenchymal tumors (GIMTs) originating from the muscularis propria (MP) 1–4 . Six patients underwent endoscopic muscularis dissection (EMD) for GIMTs originating from the MP in our institute between September 2017 and August 2019.…”
Section: Brief Explanationmentioning
confidence: 99%